DAMPAK BISNIS ISLAMI DALAM MENDORONG PERTUMBUHAN EKONOMI BERBASIS GENDER: STUDI BIBLIOMETRIK - Purnasari , Yohanita; Asfiah, Nurul (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2025)
This study aims to analyze the influence of Islamic business on economic growth and gender equality through a bibliometric approach. Using co-occurrence analysis on indexed journal data, this study explores key trends and relationships in related literature. The results show that Islamic business principles, such as fairness and sustainability, have a positive correlation to women's empowerment and economic growth. Islamic financial instruments, such as zakat and waqf, are proven to support economic inclusiveness and address gender inequality. This research provides recommendations for adopting Islamic business ethics in global development strategies to support the achievement of the Sustainable Development Goals (SDGs).